EXPLORING THE EFFICACY FACTORS OF CHATGPT IN ENHANCING INDONESIAN TO ENGLISH TRANSLATION SKILLS - Haryanti, Dwi (Prosiding University Research Colloquium, 2024)
The This study explores the effectiveness of utilizing ChatGPT for enhancing students' translation skills from Indonesian to English, focusing on seven key factors. Firstly, ChatGPT's accuracy and language proficiency enable students to produce translations with precision and grammatical correctness, facilitating language comprehension. Secondly, the provision of instant feedback and correction by ChatGPT fosters a more efficient learning process, prompting students to recognize and rectify errors promptly. Additionally, the accessibility and convenience of ChatGPT empower students to access translation assistance anytime and anywhere, promoting independent learning. Moreover, ChatGPT's customization and adaptability cater to students' diverse needs and preferences, enhancing engagement and motivation. Furthermore, the engagement and motivation fostered by ChatGPT contribute significantly to students' learning outcomes, making the learning experience more enjoyable and rewarding. Continuously, the role of ChatGPT in providing supplementary learning tools is essential for students' continuous improvement in translation skills, facilitating regular practice and refinement. Overall, integrating ChatGPT into language learning environments empowers students to develop their translation skills effectively and efficiently.